Youth athlete development and nutrition - Desbrow, B. (Sports Medicine, 2021)
Adolescence (ages 13-18 years) is a period of significant growth and physical development that includes changes in body composition, metabolic and hormonal fluctuations, maturation of organ systems, and establishment of nutrient deposits, which all may affect future health. In terms of nutrition, adolescence is also an important time in establishing an individual`s lifelong relationship with food, which is particularly important in terms of the connection between diet, exercise, and body image. The challenges of time management (e.g., school, training, work and social commitments) and periods of fluctuating emotions are also features of this period. In addition, an adolescent`s peers become increasingly powerful moderators of all behaviours, including eating. Adolescence is also a period of natural experimentation and this can extend to food choice. Adolescent experiences are not the same and individuals vary considerably in their behaviours. To ensure an adolescent athlete fulfils his/her potential, it is important that stakeholders involved in managing youth athletes emphasize eating patterns that align with and support sound physical, physiological and psychosocial development and are consistent with proven principles of sport nutrition.